Proteus vulgaris من Asparaginaseتنقية وتوصيف انزيم - رياض عباس, لميس محمد (Al-Nahrain Journal of Science, 2012)
The enzyme was extracted from Proteus vulgaris and partially purified by many steps including precipitation with ammonium sulfate by using different saturation percentages; the optimum percent was 80% gave value of specific activity 0.86 U/mg protien. then ion exchange chromatography by DEAE-cellulose column, the specific activity 2.7 U/mg protien, and gel filtration using Sephadex G-200 column specific activity 6U/mg protein. Characterization showed that the optimum pH and temperature for enzyme activity 7.5,37